ANALYSIS OF SIXBAR LINKAGE APPLICATION TO GLOBE VALVE - FAROOQ, I AZAM (2019)
Bellow sealed valves are used in industry to achieve zero leakage from any fluid system. Metal Bellow provides the characteristic of no emission sealing by extending or compressing within elastic limit while allowing the required motion to operate valve. To keep the motion of bellow with in elastic limit during compression or extension, long length of bellow is required, which in return increases the length of shaft and height of valve.